Pemberdayaan Masyarakat Melalui Pembuatan Jamu Tradisional Dalam Meningkatkan Kesejahteraan Di Kampung Jamu Nguter Kabupaten Sukoharjo - Erni Dwi Astuti; Utsman Utsman (Lifelong Education Journal, 2021)
The purpose of this study is to describe the planning, implementation, results of empowerment, as well as supporting and inhibiting factors of empowerment through making traditional herbal medicine in Kampung Jamu Nguter. The method used in this research is a qualitative approach. Data collection techniques used were interviews, observation, and documentation. The data validity technique is using source triangulation. Data analysis techniques include: data reduction, data presentation, and drawing conclusions. The results of the empowerment research through the making of traditional herbal medicine in Kampung Juter Nguter can be known in general is the planning stage is carried out in coordination with the Government and the Office. The activities carried out by training and seminars, the process of making herbal medicine starts from the selection of raw materials to the packaging and distribution process. The results of empowering increased economic income, entrepreneurship is the main livelihood of residents. Meetings and gathering are held once a month. The series of empowerment activities is an activity that aims to improve welfare in terms of economic, social, and cultural. Inhibiting factors such as the supply of raw materials is difficult due to weather factors, while supporting factors from government assistance in the form of machine tools.